Alterations in Blaood Profiles and Spleen Tissue Following Purple Sweet Pota-to Anthocyanin Extract Treatment in Restraint-Stressed Mice: Blood Profiles and Spleen Tissue Following Purple Sweet Potato Anthocyanin Extract Treatment - Kurnianingsih, Nia; Artamevia, Dian; Hasanah, Dian; Harbiyanti, Novita Titis; Ratnawati, Retty (Journal of Tropical Life Science, 2024)
Stress is associated with broad changes in blood and immune cell dysfunction, which are correlated with the spleen as a secondary lymphoid organ. Anthocyanin, a plant bioactive compound from purple sweet potatoes, has previously been reported to have a beneficial effect on stress response behavior. However, the limited studies evaluated anthocyanin's effect on blood profiles and spleen tissue under stress. Therefore, this study aimed to explore the effect of total anthocyanin extract (ANC) from purple sweet potatoes (PSP) on the blood profiles and spleen tissue of restraint stressed mice. A total of 20 male adult BALB/c mice were divided into control (CTRL), stress (STR), stress + ANC 10 mg/kgBW (STR+ANC10), stress + ANC 20 mg/kgBW (STR+ANC20), and stress + ANC 40 mg/kgBW (STR+ANC10). Restraint stress was applied two hours/day for 14 days. An automatic blood analyzer was used for blood profiling. Immunoblotting of caspase-3 and hematoxylin-eosin-stained histological slides were observed for spleen tissue analysis. Combination of STR and ANC treatment reduced the erythrocyte count, hemoglobin level, and leucocyte count. The ANC-treated groups had a higher percentage of lymphocytes and a lower percentage of granulocytes. The expression of caspase-3 declined among ANC-treated groups. Spleen extramedullary erythropoiesis, vacuolization, and white pulp involution were demonstrated in stress and ANC-treated animals. In summary, restraint stress modified the blood cell profiles and spleen tissue in the mice model. Further research is necessary to evaluate the mechanism of ANC during stress on blood cells and splenic tissue repair enhancement.